Factors Related with the Incidence of Severe Preeclampsia at the Hospital Dr M Djamil Padang - Nissa Prima Sari; Bobby Indra Utama; Meilinda Agus (Journal of Midwifery, 2017)
Preeclampsia is a condition characterized by an increase in maternal blood pressure of at least 140/90 mmHg accompanied by proteinuria and other symptoms that occur after 28 weeks gestation. The incidence of preeclampsia in hospital DR M Djamil Padang reached 33%. The exact cause of preeclampsia remains unknown, but extreme maternal age, nulliparity, history of hypertension are suspected to be the risk factors for this. This study aims to determine the factors related with the incidence of severe preeclampsia in the hospital DR M. Djamil Padang.This was observational analytic study with case control study design. The population is divided into two, the case population (all mothers with severe preeclampsia) and the control population (all mothers with no severe preeclampsia). The sample was 85 people taken by simple random sampling with the comparison between case : control (1:1). Data were taken from the patient's medical records. Data analysis was performed using univariate and bivariate using  Chi square test with  p value < 0,05.The results of this study showed there was a relationship between age (p = 0,001), parity (p = 0,020) and history of hypertension (p = 0,003) with the incidence of severe preeclampsia in the hospital DR M Djamil Padang. While the factor that has no significant relation is multiple pregnancy.Mothers with age <20 years old or ≥35 years old, nulliparity, and having a history of hypertension are more at risk for severe preeclampsia. Therefore it is expected for health workers especially midwives to increase awareness to patients especially for those who at risk of  preeclampsia.